2009
DOI: 10.3390/medicina45030031
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of knowledge and activities of primary health care professionals in promoting breast-feeding

Abstract: Summary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 14 publications
1
25
1
3
Order By: Relevance
“…Such finding has also been reported in many other countries [54,55]. In 2003, the WHO proposed that the pre-service curriculum for all health workers should provide appropriate information and advice on infant feeding for families [56].…”
Section: The Importance Of Health Care Professionals' Attitudes and Asupporting
confidence: 66%
“…Such finding has also been reported in many other countries [54,55]. In 2003, the WHO proposed that the pre-service curriculum for all health workers should provide appropriate information and advice on infant feeding for families [56].…”
Section: The Importance Of Health Care Professionals' Attitudes and Asupporting
confidence: 66%
“…Substantial gaps in the knowledge and skills to support breastfeeding of the Irish health care professionals were reported in this study; and participants suggested strengthening the training on breastfeeding among health care professionals. Such nding has also been reported in many other countries [56,57]. In 2003, the WHO proposed that the pre-service curriculum for all health workers should provide appropriate information and advice on infant feeding for families [58].…”
Section: Discussionmentioning
confidence: 65%
“…18 En diferentes estudios, el 35% de los participantes respaldaron la lactancia materna exclusiva durante los primeros seis meses de vida, y el 27,5% y el 36% fomentaban continuar con la lactancia hasta los dos años. 19,20 Ramakrishnan y cols., observaron que el 32,7% de las madres atendidas por obstetras y el 44,8% de las madres atendidas por pediatras tenían la percepción de que el profesional de la salud les había recomendado la lactancia materna exclusiva durante el primer mes de vida solamente. 21 En nuestro estudio, se observó que la mayoría de los participantes (94,9%) respaldaban la lactancia materna exclusiva durante los primeros seis meses y que el 84,8% fomentaban continuar con la lactancia materna hasta los dos años.…”
Section: Discussionunclassified